The Influence of the SAS Method (Synthetic Analytical Structural) to Improve the Vocabulary Mastery Ability of Grade I Students in Elementary Schools - Ningsih, Apriani Ayu; Marzoan, Marzoan; Fitriana, Maulida Arum (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is a quantitative study to determine the effect of the SAS (Synthetic Structural Analytical) method to improve the vocabulary mastery abilities of class I students in elementary schools in the 2023/2024 academic year. Tebayak Hamlet, Tegal Maja Village, Tanjung District, North Lombok Regency. In this type of quantitative research, the pretest approach uses a single group pretest and posttest design. The collection technique used by researchers is pretest and also uses observation, interviews and instrument tests, which shows students' ability to master vocabulary.This is proven by the average pre-test score of 53.5% while the post-test average is 76.0%. Likewise, the results of the calculations obtained are t calculated at 12.795 > t table 0.444 with a significance of 5%, thus t calculated > t table, it can be concluded that there is a significant influence of the SAS (Synthetic Structural Analytical) method to improve students' vocabulary mastery abilities. class I in elementary school.